Implementation of Web Based Leave Information System at PT Arutmin Indonesia Tambang Kintap - Maulana, Dhiya Ulhaq; Supriyanto, Arif; Utomo, Hendrik Setyo; Rahmanto, Oky (Brilliance: Research of Artificial Intelligence, 2024)
Leave is one of the rights that must be given to employees by a company. The leave application process at PT Arutmin Indonesia Tambang Kintap is still done manually, starting from the leave application to the results of the leave decision. The process of checking employee leave balances, leave applications, approvals and leave reports still relies on previous leave files. This kind of management process is often complained about because it is felt to be less effective and efficient when searching, changing, deleting data and data redundancy often occurs. Therefore, the aim of this research is to build and implement an employee leave information system which is expected to be able to help the process of managing leave in the Company. This information system was designed using ERD, DFD using the waterfall system development model. This system was built based on a website using the My database. SQL Based on the results of system functionality testing, this leave information system can function well without any problems.